Neutral Inventions and Production Functions - Sato, R.; Beckmann, M. J. (Review of Economic Studies, 1968)
R. Sato, M. J. Beckmann; Neutral Inventions and Production Functions1, The Review of Economic Studies, Volume 35, Issue 1, 1 January 1968, Pages 57–66, htt